Hashtagit merkityksien rakentajina suomenkielisissä Instagram-päivityksissä - Rosenberg, Jutta (AFinLAn vuosikirja, 2019)
This article examines ways in which Finnish Instagram users employ hashtags in their posts. Hashtags are not used only to link posts with the same tag together but also to guide readers ́ interpretations. The research material consists of 1,500 Instagram posts by private Instagram users with open accounts who have written their updates mainly in Finnish language. Findings indicate that the Finnish users employ hashtags 1) as topic tags, to highlight the subject and theme of the post; 2) as additions, to provide the necessary information for the interpretation of the post; and 3) as evaluative meta comments regarding the emotions connected with the post, the values of the writer and the tone of the post. The study has implications for the understanding of everyday construction of meaning in social media.
Keywords: kielenkäyttö; sosiaalinen media; aihetunnisteet; Instagram